2020
DOI: 10.1186/s40164-020-00161-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of recurrent gene mutations in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a genetically heterogeneous clonal malignancy characterized by recurrent gene mutations. Genomic heterogeneity, patients' individual variability, and recurrent gene mutations are the major obstacles among many factors that impact treatment efficacy of the AML patients. With the application of cost-and time-effective next-generation sequencing (NGS) technologies, an enormous diversity of genetic mutations has been identified. The recurrent gene mutations and their important roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 124 publications
1
31
0
2
Order By: Relevance
“…These mutations are also present in 20% of patients with myelodysplastic/myeloproliferative neoplasm (MDS/MPN) [ 41 ] and in 15% of patients with chronic myeloid leukemia (CLL) [ 58 60 ] . More recently, SF3B1 mutations have been identified at relatively high frequency in some solid tumors, such as various pigmented tumors, including uveal melanoma (UM) [ 61 , 62 ], mucosal melanoma [ 63 ], leptomeningeal melanoma [ 64 ] and blue nevus-like cutaneous melanoma [ 65 ], and neuroblastomas that arise following chromothripsis [ 66 ], estrogen receptor-positive breast cancers (BC) [ 67 ], pancreatic ductal adenocarcinoma [ 68 ], prostate cancer [ 69 ], prolactinomas [ 70 ], acute myeloid leukemia [ 71 , 72 ], and many others [ 73 75 ].…”
Section: Sf3b1 Mutations In Cancermentioning
confidence: 99%
“…These mutations are also present in 20% of patients with myelodysplastic/myeloproliferative neoplasm (MDS/MPN) [ 41 ] and in 15% of patients with chronic myeloid leukemia (CLL) [ 58 60 ] . More recently, SF3B1 mutations have been identified at relatively high frequency in some solid tumors, such as various pigmented tumors, including uveal melanoma (UM) [ 61 , 62 ], mucosal melanoma [ 63 ], leptomeningeal melanoma [ 64 ] and blue nevus-like cutaneous melanoma [ 65 ], and neuroblastomas that arise following chromothripsis [ 66 ], estrogen receptor-positive breast cancers (BC) [ 67 ], pancreatic ductal adenocarcinoma [ 68 ], prostate cancer [ 69 ], prolactinomas [ 70 ], acute myeloid leukemia [ 71 , 72 ], and many others [ 73 75 ].…”
Section: Sf3b1 Mutations In Cancermentioning
confidence: 99%
“…Some of these, called “High Molecular Risk” (HMR) mutations (e.g., in ASXL1 and SRSF2 ), are associated with a worse prognosis and leukemic transformation 4 . Moreover, other pathogenic variants affecting genes such as TET2 , TP53 , and FLT3 are related to preleukemic and leukemic conditions 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by malignant clonal hematopoietic stem/progenitor cell disease. About 70–90% MDS patients has one or more gene mutations 1 3 . A number of studies have confirmed that gene mutations play important role in the occurrence, development, treatment and prognosis in MDS patients 2 6 .…”
Section: Introductionmentioning
confidence: 99%